ENHANCING ACADEMIC AND INTERPERSONAL COMMUNICATION SKILL: A STUDY ON A UNIVERSITY STUDENTS AND ENGLISH LEARNERS IN PARE - Harum Mustika; Hengki Hengki; Ratna Ratna; Nazar Hasby (Journal of English Teaching, Applied Linguistics and Literatures (JETALL), 2025)
This research is aimed to improve students’ speaking skill in both academic and interpersonal communication skill through their experience in University and Course. The subject of this research are University students’ in UNISKA and English students’ in Pare that both learn and study english. The researcher used Evaluation Sheet and Interview to obtain the data. To collect the data the researcher conduct interview to the participants which had been selected by using interview guide as an instrument.is a technic which according to Koentjaraningrat “interview is a method used for a specific task, trying to obtain information and verbally forming respondents, to communicate directly”.  The interview process will be conduct by finding by identifying and select university students actively participating in English courses, as well as students from English courses in Pare. Continue by contacting university students and Pare students to explain the research objectives and request their consent to participate in the interview. Then, prepare an interview guide covering questions related to their experiences in English courses, the influence on their communication skills, and suggestions for improvement.